Frequency of low back pain in young adults and its relationship with different mattresses - Mudassar Rooh Ul Muazzam; Abbas, Salma; Abbas, Sidra; Rafi, Muhammad Ashar (Journal of the Pakistan Medical Association, 2021)
Objective: The purpose of this study was to find out the frequency of low back pain in young adults and its relationship with the mattresses they use. Methodology: This cross sectional study was carried out in 6 months in twin cities (Rawalpindi and Islamabad). The sample size for this study was 366. For data collection, self-structured questionnaire was used along with Modified Oswestry Scale and Numeric Pain Rating Scale (NPRS). The inclusion criteria for this study was young adults with age limit 18-35 years and the participants who used the same kind of mattress for more than 3 months. Post-surgical patients and the patients diagnosed with lumbar pathology were excluded from this study. Data was then analyzed through SPSS statistics 24. Results: Mean age of the participants was 22.06±3.74 years. Majority 208(56.38%) participants were feeling low back pain and out of these 208 participants, Pain was most prevalent 30(68.18%) in firm mattress users followed by 128(59.25%) in foam mattress users. Low back pain was more associated with those participants who were not changing their mattresses for more than three years. Conclusion: Low back pain is frequently present in young adults and more prevalent in those participants who were using same firm or foam mattresses for more than three years. Keywords: Back pain, Mattresses, Posture, and Young Adults. Continuous...